Leadership language practices of the Prophet Mohamad (PBUH) to sustain marriage relationship through Aisya’s narration - Abdullah, Ariza; Abdul Jabar, Mohd. Azidan; Mustapha, Nik Farhan; Toklubok @ Hajimaming, Pabiyah (Global Academic Excellence, 2019)
A family unit needs a good leader to produce quality human resources and better experiences in relationships. A critical analysis in the discourse of the Prophet should be undertaken to discover his showmanship of a great leader in the family. The analysis of hadith discourse in the critical perspective of the language of the Prophet Muhammad’s (PBUH) marriage life is still less given attention rather than general analysis of the prophet’s leadership. The purpose of the study is to identify leadership language practices through textual narration and thus, interpret hadith discourse through discursive study to explain the practices. Eleven hadith related by Aisya R.A was selected to show the leadership language during their marriage. Analysis is conducted using Fairclough’s threedimensional model in critical discourse analysis. The method links between linguistics characters and social practice through discourse practices. Findings discover seven forms of languages being practiced by the Prophet to sustain the marriage and bring happiness to all his wives. The Prophet Mohammad (PBUH) was found to use different practices of language according to context of situation. Seven practices identified are negational language, assertive language, request language, nonverbal language, figurative language, expressive language and negation and declarative language. This study is an effective example to the community to build a stronger domestic institution.